STUDENTS’ DIFFICULTIES IN TRANSLATING NARRATIVE TEXT FROM ENGLISH INTO INDONESIA AT IAIN BUKITTINGGI - Yenita Hastuti; Absharini Kardena; Eliza Chio (Universitas Islam Negeri Alauddin Makassar, 2020)
The research is due to several problems found in the field; the students assumed that narrative text was the difficult text to translate. It happened because the students translate the text literally, also the students were lack of vocabularies in translating the text. This research aims to find out the causes of students’ problems in translating narrative text. The research used descriptive method with a quantitative approach in which the sample of the research was 55 fifth semester students of English Education Study Program at IAIN Bukittinggi, academic year 2018/2019, by using questionnaires as the instrument of this research. The findings of the research showed that there are two factors causing problems in translating narrative text from English into Indonesian; they are linguistic factors and non-linguistic factors. It is proved by the highest percentage of students’ difficulties which is 55% in linguistic factors and 52% in non-linguistic factors.